2021
DOI: 10.17977/um025v5i22021p73
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation Of The Leadership Role Of School Principal

Abstract: This study aims to evaluate the leadership role of school principals in Ensino Secundario Geral Cristal. This type of research is descriptive qualitative by using the Discrepancy evaluation model. Data collection techniques using interviews, observation, and documentation. The results showed that (1) the design component has a category that shows the role of principal leadership using management with good planning to make initial programs under the mission and vision in the learning process; (2) the installati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…Moreover, in managing the organization, these psychological attributes have a dominant influence on the success of the managers. Some local research results showed that the characteristics of managers or leaders affect the organization's performance [24,42]. Other research from several countries also indicated the same results [45][46][47][48][49].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Moreover, in managing the organization, these psychological attributes have a dominant influence on the success of the managers. Some local research results showed that the characteristics of managers or leaders affect the organization's performance [24,42]. Other research from several countries also indicated the same results [45][46][47][48][49].…”
Section: Discussionmentioning
confidence: 81%
“…This is in line with the theory that perception is within the individual. Starting with a positive perception will lead to good behavior, and good behavior will be able to translate to the success of program implementation [42,43]. Therefore, this explains why this variable has a weaker effect than the other variables.…”
Section: Discussionmentioning
confidence: 99%